Vaccines: New challenges, new paradigms, new opportunities: Report of the 22nd DCVMN Annual General Meeting. Issue 26 (9th June 2022) - Kumar Suri, Rajinder; Hayman, Benoit; Prasad, Sai D.; Makhoana, Morena; Tippoo, Patrick
Highlights: Partnerships and collaborations key to mitigate the effects of the COVID-19 pandemic and to prepare for future pandemics. The inequitable access to COVID-19 vaccines is a failure of humanity and will continue to have significant economic and health consequences if not addressed. Deliberate actions are required to establish sustainable vaccine manufacturing on the African continent. Innovative vaccine technologies, regulatory and financing mechanisms are critical to strengthening global health security. Abstract: The Developing Countries Vaccine Manufacturers Network held its 22nd Annual General Meeting in October 2021. Vaccine manufacturing experts, leaders from global public health organizations and dignitaries from governments and multilateral organizations discussed the challenges and opportunities emerging from the COVID-19 pandemic. Over 350 delegates from 33 countries, representing over 70 organizations partook in the meetings deliberations. The development and scaled-up production of several safe and effective vaccines against COVID-19 resulted in over 12 billion doses being produced by the end of 2021. Unfortunately, this scientific achievement and outstanding industry effort has been overshadowed by the striking inequity in access to COVID-19 vaccines. High and upper middle-income countries have received 75% of the vaccines, while in Africa, less than 5% of the people are fully vaccinated. The inequitable access to vaccines is an issue of national health security, which has stressed the need to establish local vaccine manufacturing capacity in Africa. Key partnerships, initiatives and the deliberate strategies required to achieve sustainable manufacturing on the continent were discussed. The ability to acquire technology, access markets and financing mechanisms, and workforce development were reported as key enablers to achieving a healthy ecosystem. Innovative vaccine technologies, new regulatory approaches, and the importance of voluntary technology transfers in increasing the global supply capacity of both COVID-19 vaccines and traditional vaccines were highlighted. In reviewing the lessons learned from the pandemic, speakers shared a consensus that innovation and partnerships will be central to any solution proposed to mitigate the current pandemic and prepare for future ones.